2020
DOI: 10.1093/cercor/bhaa106
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Entopeduncular Nucleus and the Globus Pallidus to the Control of Locomotion and Visually Guided Gait Modifications in the Cat

Abstract: We tested the hypothesis that the entopeduncular (EP) nucleus (feline equivalent of the primate GPi) and the globus pallidus (GPe) contribute to both the planning and execution of locomotion and voluntary gait modifications in the cat. We recorded from 414 cells distributed throughout these two nuclei (referred to together as the pallidum) while cats walked on a treadmill and stepped over an obstacle that advanced towards them. Neuronal activity in many cells in both structures was modulated on a step-by-step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 97 publications
2
13
1
Order By: Relevance
“…In those studies that have recorded activity to movement of the ipsilateral limb (DeLong, 1971;Iansek and Porter, 1980;Wannier et al, 2002), only relatively few (,30%) of cells were active for both contralateral and ipsilateral movements. However, in our recent locomotor study (Mullié et al, 2020), we found a much larger proportion of cells that discharged in relationship to the gait modifications of the ipsilateral limb. Possibly this contribution to the control of each forelimb may be specific to locomotion in which the movement of the two forelimbs (and, of course, the hindlimbs) is obligatorily coupled.…”
Section: Introductioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In those studies that have recorded activity to movement of the ipsilateral limb (DeLong, 1971;Iansek and Porter, 1980;Wannier et al, 2002), only relatively few (,30%) of cells were active for both contralateral and ipsilateral movements. However, in our recent locomotor study (Mullié et al, 2020), we found a much larger proportion of cells that discharged in relationship to the gait modifications of the ipsilateral limb. Possibly this contribution to the control of each forelimb may be specific to locomotion in which the movement of the two forelimbs (and, of course, the hindlimbs) is obligatorily coupled.…”
Section: Introductioncontrasting
confidence: 53%
“…Tasks and training. Experiments were performed on two male cats (BG5 and BG6, weight 5.6 and 5.0 kg, respectively) that were initially trained to walk on a treadmill at a speed of 0.45 ms À1 and to step over two obstacles attached to that treadmill (Mullié et al, 2020). They were subsequently trained to perform a task in which they reached forward and depressed a lever with either the left or right forelimb (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesioning or inactivation studies were largely inconclusive, as these manipulations did not result in a consistent motor phenotype (Norton, 1976;Ossowska et al, 1983;Schneider and Olazabal, 1984;Hauber et al, 1998;Joel et al, 1998;Konitsiotis et al, 1998;Soares et al, 2004;Hegeman et al, 2016). A large number of studies showed that GPe neurons change their activity in relation to movement; however, the identity of the recorded neurons was unknown (DeLong, 1971;Anderson, 1978;Anderson and Horak, 1985;DeLong et al, 1985;Mink and Thach, 1987;Mitchell et al, 1987;Filion et al, 1988;Nambu et al, 1990;Mink and Thach, 1991b, a;Mushiake and Strick, 1995;Parent and Hazrati, 1995;Kimura et al, 1996;Arkadir et al, 2004;Shin and Sommer, 2010;Schmidt et al, 2013;Yoshida and Tanaka, 2016;Gu et al, 2020;Mullie et al, 2020). It has been shown that identified GPe neuron subtypes can display diverse changes in their activity during spontaneous body movements (Dodson et al, 2015).…”
Section: Gpe Neuron Subtypes Have Opposing Roles In Motor Controlmentioning
confidence: 99%
“…Reticulospinal neurons integrate sensory inputs and carry the locomotor command sent monosynaptically by the Mesencephalic Locomotor Region (MLR), a brainstem region that controls the initiation and speed of locomotion (Sirota et al, 2000 ; Ryczko et al, 2016a ; Caggiano et al, 2018 ; Josset et al, 2018 ; for review Ryczko and Dubuc, 2013 ). The MLR is under tonic inhibitory control of the output structures of the basal ganglia (Roseberry et al, 2016 ), which are involved in action selection, as well as planning and executing of gait modifications (Stephenson-Jones et al, 2011 ; Mullié et al, 2020 ; for review Grillner and Robertson, 2016 ). Dopaminergic nuclei influence the activity of the MLR indirectly through ascending projections to the basal ganglia (Kravitz et al, 2010 ), and directly through descending projections to the MLR (Ryczko et al, 2013 , 2016b ; Pérez-Fernández et al, 2014 ; Sharma et al, 2018 ), and the spinal cord (Koblinger et al, 2018 ; for review Fougère et al, 2019 ).…”
Section: The Locomotor Systemmentioning
confidence: 99%